2019
DOI: 10.1002/jcb.28924
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis reveals the changes of circular RNA expression and molecular mechanism in acute lung injury mouse model

Abstract: Acute lung injury (ALI) is a severe disease with sudden onset, rapid progression, poor treatment response, and high mortality. An increasing number of studies had found that circular RNAs (circRNAs) has significant functions in various diseases, while the role of circRNAs in ALI is not yet clear. The purpose of this study was to find circRNAs related to ALI and their mechanism of action. Expression profiles of lung circRNAs and messenger RNAs (mRNAs) were analyzed by microarray in the ALI mice models and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…This in ALI model mice, compared with normal mice via cricRNA microarray analysis. 14 To the best of our knowledge, the study presented in this report is the first investigation to explore the role of circC3P1 in ALI induced by sepsis. Such findings may offer important insights into the treatment of ALI.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This in ALI model mice, compared with normal mice via cricRNA microarray analysis. 14 To the best of our knowledge, the study presented in this report is the first investigation to explore the role of circC3P1 in ALI induced by sepsis. Such findings may offer important insights into the treatment of ALI.…”
Section: Discussionmentioning
confidence: 87%
“…Circular RNAs (circRNAs), a novel type of noncoding endogenous RNAs, can modulate the gene expression post‐transcriptionally via serving as miRNA sponges 13 . Recently, Li et al have reported the changes of circRNAs level and potential molecular mechanism in the ALI mice model by microarray analysis, suggesting that circRNAs make a vital contribution to the development of ALI 14 . CircC3P1 was derived from exons 27 to 29 of complement component 3 precursor pseudogene (C3P1) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Increasing evidence has shown that circRNAs can regulate gene transcription by functioning as a competing endogenous RNA (ceRNA). 20,21 circRNA can sponge microRNA (miRNA) with functional miRNA binding sites and then inhibit miRNA activity to release inhibited target genes of mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only two studies have shown the involvement of circRNAs in sepsis-induced ALI. Li et al 21 observed significantly changed circRNA profiles and revealed a potential role of circRNAs in a mouse model of LPS-induced ALI. Bao et al 22 reported many circRNAs of dysregulated expression in the pulmonary macrophages of mice with sepsis-induced ALI.…”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, the circRNA expression profile has been analyzed in the context of a variety of respiratory diseases, including lung cancer, 20,21 pulmonary fibrosis, 22 pulmonary tuberculosis 23 and acute lung injury. 24 To date, the expression profile and ceRNA network of circRNAs in COPD patients have been largely unexplored.…”
Section: Introductionmentioning
confidence: 99%